An Addition of Ethanol and Patchouli Oil on Pertamax: The Case Study of Their Effect on Exhaust Gas Emission for 4-stroke Engine - Mohammad Farhan; Adhes Gamayel (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2023)
Industrial sector has been focused on the transportation and automotive service due to their essential for many people in every daily life. Currently, almost everyone has a motorized vehicle which also has an effect on improving the country’s economy. On the other hand, this raises concerns about the occurrence of a global warming phenomenon. The more motorized vehicles were extremely impact on increasing the exhaust gasses that also have a negative impact to the environment, including carbon monoxide (CO) and carbon dioxide (CO2). Hence, this work tried to reduce the exhaust gas emission through the addition of ethanol and synthetic additive, namely patchouli oil. This case study was conducted using pertamax fuel with octane number 92. We analyzed five different optimization sample that consisting of S1, S2, S3, S4, and S5. Then, the several characterizations also carried out to these samples for supporting the results obtained i.e. density, viscosity, and surface tension. Also, the variation of engine rotation speed (in rpm) is utilized to determine the performance or the impact of the samples made to the environment. The results indicate that the pertamax sample mixed with ethanol and patchouli oil showed an optimal performance in S5, there is no detect of CO emission. Then, S3 for the lowest emission of CO2. Also, S3 for the highest efficient in fuel consumption. Hoping this work has an extremely impact for the reducing an exhaust emission in fuels and increasing the energy efficient of internal combustion engines